2008
DOI: 10.1038/ng.171
|View full text |Cite
|
Sign up to set email alerts
|

Systematic meta-analyses and field synopsis of genetic association studies in schizophrenia: the SzGene database

Abstract: In an effort to pinpoint potential genetic risk factors for schizophrenia, research groups worldwide have published over 1,000 genetic association studies with largely inconsistent results. To facilitate the interpretation of these findings, we have created a regularly updated online database of all published genetic association studies for schizophrenia ('SzGene'). For all polymorphisms having genotype data available in at least four independent case-control samples, we systematically carried out random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
765
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 964 publications
(802 citation statements)
references
References 39 publications
22
765
1
10
Order By: Relevance
“…To our knowledge, the 8p23.3-p23.1 deletion and 19p13.3-p13.2 duplication have not been previously reported. There are other chromosomal abnormalities associated with schizophrenia that involve these regions (Bassett et al, 2000); however, there is no direct overlap with linkage or "top" association findings highlighted in the January 2010 SzGene Database (Allen et al, 2008). There are 11 genes in the 8p23.3-p23.1 region and approximately 250 genes in the 19p13.3-p13.2 region.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the 8p23.3-p23.1 deletion and 19p13.3-p13.2 duplication have not been previously reported. There are other chromosomal abnormalities associated with schizophrenia that involve these regions (Bassett et al, 2000); however, there is no direct overlap with linkage or "top" association findings highlighted in the January 2010 SzGene Database (Allen et al, 2008). There are 11 genes in the 8p23.3-p23.1 region and approximately 250 genes in the 19p13.3-p13.2 region.…”
Section: Discussionmentioning
confidence: 99%
“…26 Within SLC6A4, STin2 has been reported to be the strongest candidate polymorphism showing susceptibility to schizophrenia. 17,27 The STin 2.12 allele has been reported to have increased vulnerability to schizophrenia. [28][29][30][31] These observations are consistent with current results.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the mapping of the human genome, identification of genetic determinants of complex psychiatric disorders such as schizophrenia, major depression or bipolar disorder has proven challenging (Allen et al., 2008). Indeed, genome‐wide association studies (GWAS) have shown that these disorders are highly polygenic (Barnett & Smoller, 2009; Schizophrenia Working Group of the Psychiatric Genomics, 2014; Shyn et al., 2011) with many genes exerting their influence on numerous neural pathways involved in complex aspects of brain function and likely being impacted upon by environmental events.…”
Section: Introductionmentioning
confidence: 99%